A brief history of the Open Discovery Initiative. Issue 1 (7th December 2016) - Varnum, Kenneth J.
Abstract : Key points The Open Discovery Initiative (ODI) was created in 2011 to improve participation among content providers in the then‐novel web‐scale discovery services. The issues addressed by the ODI included metadata standards, content indexing, and availability of licensed content in discovery services. After adoption of the recommended practice in June 2014, a new Standing Committee has been formed to address unfinished business and implementation. A challenge for the ODI is finding the right balance between the needs of commercial partners and library customers.